2019
DOI: 10.1200/jco.2019.37.15_suppl.11027
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of extra-skeletal versus skeletal Ewing sarcoma patients treated with standard chemotherapy protocol.

Abstract: 11027 Background: Extra-skeletal ewing sarcomas (ES) are rare, and data on outcomes following standard ES chemotherapy protocols are very limited. Methods: We retrospectively collected data on skeletal and extra-skeletal ES patients who presented with localized disease from January, 2006 to June, 2018. Disease and treatment characteristics were compared between the two groups by the chi-square test. Overall survival (OS) and local recurrence free survival (LRFS) were estimated by the Kaplan-Meier method and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Of the total of 346 suspected ESFT, 44 (20), leg (4), popliteal fossa (2), gluteal region (5), cheek (2), orbit (2), nose and nasopharynx (2), scalp (1), neck (7), parapharyngeal (2), chest wall (29), mediastinum and thorax (5), paraspinal (20), abdomen and retroperitoneum (14). Visceral tumours were noted in 34 (22.22%) patients and the sites included ovary (4), cervix (3), vagina (1), kidney (7), bladder (2), prostate (1), lung (4), breast (5), lymph node (3), intestine (2), and brain (2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the total of 346 suspected ESFT, 44 (20), leg (4), popliteal fossa (2), gluteal region (5), cheek (2), orbit (2), nose and nasopharynx (2), scalp (1), neck (7), parapharyngeal (2), chest wall (29), mediastinum and thorax (5), paraspinal (20), abdomen and retroperitoneum (14). Visceral tumours were noted in 34 (22.22%) patients and the sites included ovary (4), cervix (3), vagina (1), kidney (7), bladder (2), prostate (1), lung (4), breast (5), lymph node (3), intestine (2), and brain (2).…”
Section: Resultsmentioning
confidence: 99%
“…7 , 12 , 18 - 22 Furthermore, involvement of the extremities between skeletal and extra-skeletal tumours was observed to be statistically significant in our study. Salah et al 14 reported soft tissue location in 23 (79%). Visceral ESFTs have been described in studies with small sample size, ranging from 29 to 58 with percentage of such cases varying from 6% to 21% ( Table 3 ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations